(untitled) (Boletín Epidemiológico Semanal, 2025)
Introduction: The Spanish Acute Respiratory Infections surveillance system (SiVIRA) was set up in the 2020-21 season with gradual implementation in Spanish autonomous communities and cities. We here present the results of SiVIRA for the 2023-24 season. Method: Within syndromic surveillance, all cases who presented with acute respiratory infection in primary care (ARI) or were admitted for severe ARI (SARI) in hospitals were collected, allowing calculation of weighted weekly incidence rates. A systematic and representative sample of syndromic cases was selected for microbiological study, allowing calculation of positivity rates for influenza, SARS-CoV-2 and respiratory syncytial virus (RSV). Results: ARI and SARI incidence rates reached their maximum, respectively, in week 52/2023 (968.7 cases per 100,000 inhabitants), and week 01/2024 (38.7 cases per 100,000). The influenza epidemic was characterized by predominant circulation of influenza A, and developed between weeks 50/2023 and 04/2024, peaking in week 52/2023 or 01/2024, depending on which indicator. Two COVID-19 epidemic waves were observed, one with a peak incidence in week 51/2023 with predominance of the BA.2.86* variant (same week in which the RSV epidemic peaked) and the other one peaking in week 26/2024 coinciding with the increase of the K.P.3* variant. Discussion: In the 2023-24 season, the epidemic waves of influenza, COVID-19 and RSV coincided, and, while ARIs rates were similar to the 2022-23 season, SARI rates were considerably higher. The intensity of the seasonal epidemic was lower than the previous season for RSV, higher for influenza and similar for COVID-19.